Care and Prevention of Gender-Based Violence in Mexico City: The Case Units for Care of Family Violence - García Cervantes, Elizabeth (2018)
This paper takes up and updates information derived from my research project for Master's Degree in Women's Studies research titled “Analysis of the factors that influence the process of intervention in domestic violence at the Unit for Care and Prevention of Family Violence (UAPVIF)", which aimed to analyze the process of intervention in gender violence and the various factors that influence it. Qualitative research work was carried out to give an account of this process, using an ethnographic method; the main techniques implemented were in-depth interviews and observation. This article analyzes the circumstances in Mexico City (formerly the Federal District) that facilitated the incorporation of the issue of gender violence in the public agenda and the impact generated in the practices of attention to domestic violence from two laws on the subject. This analysis focuses on the UAPVIFs, which belong to the Government of Mexico City. The above is done within the framework of the 10th anniversary of the publication of the Law on Women's Access to a Life Free of Violence, and the next change of public administration that will take place at the end of 2018.